2007
DOI: 10.1093/ps/86.9.1980
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrogen Intake Regulates Hepatic Malic Enzyme Messenger Ribonucleic Acid Expression

Abstract: Increased dietary protein intake rapidly (3 h) decreases malic enzyme and increases hepatic histidase mRNA expression. Experiments were conducted to determine the role that individual dispensable amino acids and nonprotein N sources might have in regulating the activity of these enzymes and to determine if the addition of a N supplement to a practical broiler diet during the entire rearing period would reduce abdominal fat accumulation in broilers. Broiler chicks were fed a basal diet containing 22% protein or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, using AA-to-Lys ratios corresponding to the ideal protein profile limits fat deposition; however, this phenomenon still occurs, indicating that the effect of CP on fat deposition is not solely related to AA limitations. This is consistent with the results from Chendrimada et al (2007), which showed the inhibitory effect of protein with non-essential AA (i.e., Ala and Glu) and mineral N, on the malic enzyme involved in fat deposition.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, using AA-to-Lys ratios corresponding to the ideal protein profile limits fat deposition; however, this phenomenon still occurs, indicating that the effect of CP on fat deposition is not solely related to AA limitations. This is consistent with the results from Chendrimada et al (2007), which showed the inhibitory effect of protein with non-essential AA (i.e., Ala and Glu) and mineral N, on the malic enzyme involved in fat deposition.…”
Section: Discussionsupporting
confidence: 92%
“…m-NAD-ME is a unique isoform that has a multifaceted regulatory system for control of its catalytic activity [4,6,27,28,30,32,33]. It displays substrate cooperativity in l-malate, and the enzyme can be allosterically activated by fumarate [16,30,33].…”
mentioning
confidence: 99%